Variation in the Genomic Composition of Plasmodium falciparum Merozoite Surface Proteins 1 and 2 in Nigerian Children Less Than 5 Years Old in the State of Delta (Indo-American Journal of Life Sciences and Biotechnology, 2025)
In context, Nigeria has the greatest malaria burden among African countries, and the continent itself is still the malaria hub. Pharmacogenomics, genetic reference panels, and malaria biomarkers all need an upgrade to meet the current worldwide issues of malaria resistance. Children under the age of five in certain regions of Delta State, southern Nigeria, were studied to determine the genetic diversity and structure of Plasmodium falciparum merozoite surface proteins (msps 1 and 2). Methods: Due to low parasite density, P. falciparum deoxyribonucleic acid was recovered from 86 samples that tested positive for malaria out of 690 people. The msp1 and msp2 allele genotyping was examined by electrophoresis, polymerase chain reaction, and an ultraviolet-trans illumination gel method. Findings: MAD20+RO33+K1 (67.4% of cases) and 3D7+FC27 (90% of cases) were the most common forms of polyclonal infection for msp1 and msp2, respectively. Ro33 (36.3% of the total) and FC27 (53.4% of the total) were the most common msp1 and msp2 alleles, respectively. Furthermore, the allelic makeup of the research population did not vary significantly between men and females. But msp1 had an infection multiplicity of 1.10 and msp2 had an infection multiplicity of 1.08, whereas the corresponding heterozygosity values were 0.67 and 0.50, respectively. Conclusion: In Delta State, Nigeria, a high transmission rate of P. falciparum infection was observed, suggesting a large degree of genetic middling heterozygous alleles. These results emphasize the need for targeted and locally sourced anti-malaria treatments to be developed.